Leanness and agility in the judicial supply chain - Storsjö, Isabell; Martins, A.; Zanoni, Simone (EurOMA 2015 - Operations management for sustainable competitiveness, 2015)
The lean approach, successfully applied in the manufacturing and service sectors, can be seen as an approach to reducing delays in courts. However, a straightforward application of lean can be difficult in heterogeneous environments: judicial systems typically deal with a very large number of individual and infinitely different cases. Therefore, also an agile approach to court delay reduction could be taken. The purpose of this paper is to investigate how the lean and agile supply chain strategies could be applied to the European Small Claims Procedure; moreover, the decoupling point and its essence in this context is discussed.